2022
DOI: 10.3390/molecules27196215
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils as a Source of Ecofriendly Insecticides for Drosophila suzukii (Diptera: Drosophilidae) and Their Potential Non-Target Effects

Abstract: The spotted wing drosophila (Drosophila suzukii) is one of the main invasive pests of small fruits in the world. Thus, 19 essential oils (EOs) were selected to analyze the effects through toxicity and repellency on oviposition and D. suzukii adults. In addition, their lethal and sublethal effects on the pupal endoparasitoid Trichopria anastrephae were evaluated. The EOs of C. flexuosus and Mentha spp. had the highest toxicity observed in the topical application bioassay for D. suzukii. In contrast, the EOs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In similar tests, also regarding the assessment of the repellent effects, geranium (P. asperum) was reported to be a great source of repellent for this pest [25], which is in accordance with this study. Considering geranium's complex chemical composition, it may act on more than one site, but EOs mostly affect the central nervous system, causing paralysis and death of the insects [52]. The identified major compounds found in our study were citronellol (22.16%) and geraniol (21.22%), which are most likely responsible for the insecticidal activity against D. suzukii as well [35,52].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In similar tests, also regarding the assessment of the repellent effects, geranium (P. asperum) was reported to be a great source of repellent for this pest [25], which is in accordance with this study. Considering geranium's complex chemical composition, it may act on more than one site, but EOs mostly affect the central nervous system, causing paralysis and death of the insects [52]. The identified major compounds found in our study were citronellol (22.16%) and geraniol (21.22%), which are most likely responsible for the insecticidal activity against D. suzukii as well [35,52].…”
Section: Discussionmentioning
confidence: 64%
“…Considering geranium's complex chemical composition, it may act on more than one site, but EOs mostly affect the central nervous system, causing paralysis and death of the insects [52]. The identified major compounds found in our study were citronellol (22.16%) and geraniol (21.22%), which are most likely responsible for the insecticidal activity against D. suzukii as well [35,52]. These components in the geranium essential oils might play a primary role in the mode of action against D. suzukii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that EOs may be used in both conventional and organic agriculture with little or no environmental impact, their use as bioinsecticides is of great interest [ 45 ]. Although EOs have a complex chemical composition and can act on multiple sites, most of the paralysis and death of insects caused by these mixtures is explained by damage to the central nervous system [ 46 ]. From the literature data, it has been observed that P. graveolens EO, commonly referred to as geranium EO, has insecticidal and insect-repelling qualities.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced number of effective control practices for D. suzukii has been a serious problem for cherry and berry production in the Neotropical region [ 1 , 2 , 50 , 51 , 52 , 53 ]. The reliance on a reduced number of molecules can either be worsened by the fact that some of these molecules can also have detrimental effects on non-target organisms [ 54 , 55 ]. For instance, T. anastrephae has been shown to be susceptible to the conventional insecticides used in the management of D. suzukii [ 7 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%